Evaluation of cassava mash dewatering methods - Kolawole, O.P.; Agbetoye, L.A.S.; Ogunlowo, A.S. (2011)
Using different cassava maturity age of 9, 12 and 15 months, evaluation study was carried out on cassava mash dewatering methods. Dewatering tanks with square and cylindrical shapes were made with steel for the experiment. Pressure devices from screw bolts, hydraulic jack press and rope / stick methods were used to squeezed cassava juice from the mash in the tanks. TMS 4(2) 1425 variety of cassava was used. Cylindrical tank containing a 12 months old sample with hydraulic jack gave mash cake with moisture content of the sample at 44% wet basis in the shortest time.